Social Studies Education: A Veritable Tool for Achieving Value Re-Orientation and Sustainable Development in Nigeria - Omoniyi, Mofoluwawo Esther (International Journal of Learning and Development, 2024)
Education has been viewed by the international community as a fundamental human right and key development index. A key to sustainable development, peace and stability within and among countries. The rot in Nigerian society has affected the standard of value and moral character formation, greatly. This has manifested in so many anti-social vices exhibited by the Nigerian citizens. Antisocial vices exhibited include violent crimes, lack of accountability, greed, indiscipline, corruption, disrespect to constituted authority and a host of other vices. These have posed a serious moral problem for the Nigerian state and have set back all sincere efforts targeted at achieving sustainable development goals by 2030. This paper is out to examine how social studies education can serve as a veritable tool in achieving value re-orientation and sustainable development in Nigeria. The paper adopts descriptive approach and content analysis as its methodologies. Using a systematic random sampling method, a total of 100 respondents from five secondary schools in the two local government areas within Oyo metropolis was used. The data collected was analyzed using descriptive statistics of mean and standard deviation. The paper concludes that the problem is not lack of wealth but lack of essential value system in Nigerian society and that re – orientation in educational system would lead to redemption, and as well salvage the national character and image, which would lead to vibrant economy and sustainable development. The author suggests that the re - orientation of positive values through social studies education would promote national image, respect for human and corporate values while faithful and honest individual children and citizens should be rewarded and celebrated. It is high time the Nigerian government shunned the idea of celebrating mediocrity.